Microscopic Analysis of the Rejuvenation Mechanism and Rejuvenation Effect of Asphalt Binders. (22nd September 2021) - Shan, Ke; Bao, Chonghao; Li, Dandan; Zheng, Chuanfeng
Abstract : This study investigates the rejuvenation mechanism of asphalt binders at the microscopic level and compares the rejuvenation effects of rejuvenators. A model of rejuvenated asphalt was established on the basis of molecular simulation by adding different doses of two rejuvenators to the aged asphalt. This model was validated in terms of density and surface free energy. The diffusion ability of the rejuvenator was investigated by using a diffusion model and mean square displacement. The deagglomeration ability of rejuvenators on asphaltene was explored by using a radial distribution function. The microscopic mechanism of asphalt rejuvenation was explained. Results show that small molecule structures are more diffusible than long-chain structures, and aromatic ring structures are more attracted than polar functional groups. The rejuvenating effect of the rejuvenator was evaluated in terms of viscosity and cohesive energy density. Results show that the long-chain structure reduces the viscosity value more than the small molecule structure. The aromatic ring structure in the aged asphalt helps to restore the compatibility between the fractions. This study serves as a guide for the selection and development of future rejuvenators.